The Dams and Water Management Systems of Minoan Pseira - Betancourt, Philip P. (Institute for Aegean Prehistory Press, 2012)
List of Figures; Preface; Acknowledgments; Abbreviations; 1 Introduction; 2 The Pseiran Agricultural Crisis in the Middle of the Second Millennium B.C.; 3 The Pseiran Water Management Systems; 4 Comments and Discussion; Appendix; References; Index